SISTEM INFORMASI GEOGRAFIS PEMETAAN MASJID DI SAMARINDA BERBASIS WEB - maharani, septya (Universitas Ahmad Dahlan, 2017)
The mosque was built to meet the needs of the Islamic religious community in implementing the obligations of the God Almighty. The presence of mosques that spread requires a system that facilitates the provision of information regarding the location of the mosque, the capacity of the church, the activities in mosques, the existing facilities in the mosque, as well as other information about the mosque is useful for local residents as well as residents of areas outside Samarinda. This study aims to make an application to the web-based geographic information system in order to facilitate the public in obtaining information and find the location of the mosque. The data were collected by observation and gather supporting information via the internet. The programming language used is PHP, Google Maps API as a framework, and MySQL as the database. Results of the study is a mosque-based geographic information system website, which displays information on the location of the mosque and the search for the closest distance that comes with directionsÂ Keywords: Geographic Information System, website, Mosque